Criminal mediation and its prohibition in cases of gender violence: the Spanish model - Laura Álvarez Suárez (Revista Brasileira de Direito Processual Penal, 2019)
This work aims to analyze whether it is convenient to maintain the prohibition of mediation in gender violence crimes established in the Spanish legal system. In Spain, restorative justice procedures have not yet been regulated within the criminal sphere, but this has not been an impediment for the legislator to exclude mediation in all cases of gender violence, despite the abundant criticisms from the doctrine. These have become stronger than ever after the European mandate to establish mechanisms of restorative justice; it is sustained that the new regulation should be accompanied by the express derogation of said prohibition. The stereotype of gender violence victim established by the current law allows us to argue that it would be more appropriate to abolish the prohibition and allow these victims to submit to a mediation procedure if it is their will and a series of prerequisites are also present.